Genetic variation in sesame genotypes (Sesamum indicum L.) grown in Telangana: Genetic variation in sesame genotypes (Sesamum indicum L.) grown in Telangana - D PADMAJA; T KIRAN BABU; T SHOBHA RANI; R UMA REDDY (Journal of Oilseeds Research, 2020)
The genotypic and phenotypic variability, genetic advance and heritability in a broad sense were estimated in 22 genotypes. Highest GCV and PCV was observed for seed yield/plant followed by number of capsules/plant and number of branches/plant. Among 22 entries tested, JCS 3202 and JCS 2701 cultures recorded significantly higher yield as compared to check, Hima.